Students' Anxiety in Speaking English: a Case Study in Online Classes - Gita Rahmi; Yella Dezas Perdani; Yessi Widyasari (Jurnal Sosial Humaniora dan Pendidikan, 2025)
The purpose of this study was to investigate the students’ level of anxiety in Speaking English in online classes at one university in Indonesia. The research used mix-method of quantitative and qualitative design. The quantitative data were analyzed by using The FLCAS (Foreign Language Classroom Anxiety Scale) by Horwitz et al., (1986) and qualitative data were analyzed by using Maxwell’s theory (1996). The data were categorized, coded and contextualized. There were 42 students who participated in the research. The research found that ten students were in anxious level, 23 students were in mildly anxious level and nine students were in relaxed level. The students admitted that grammar, vocabulary and pronunciation were the students’ problems in speaking. The factors caused them to have the anxiety in speaking can be categorized as communication apprehension, test anxiety and fear of negative evaluation. From the result of this research, the institution and the lecturers are expected to play major role in managing and reducing the students' anxiety. Various teaching methods and medias are hoped to make class become more interesting. Further research can be done by involving more participants and in experimental research to find out the solution to reduce the students' speaking anxiety.